Is the functional capacity crucial for position determination in the football team? - Vucetic, V.; Sukreski, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
During past twenty years, many new elements introduced in the football game have significant changed the way it is played. There are many differences between the old type of playing football and today`s modern view of football but the two most important are speed of the game and the game`s dynamic. This is why significance of conditional component in football training is very important. Guided with this thought, we have asked ourselves if there are any differences in the functional capacity between defenders, middle field players and attackers. Methods: Forty five football players (24.1±4.4 yrs; 182± 6.2 cm; 79.9 ± 7.5 kg) were divided in three groups: 15-defenders (DEF), 15-middle field players (MF) and 15-attackers (AT). Football players in this research were taken from the National team and the first Croatian football league. All subjects performed an incremental treadmill test (0.5 km/h speed increase per half minute, 1.5% grade) to volitional exhaustion, and walked at 5 km•h-1 during the first two minutes of recovery. The ANOVA was used to determine differences in observed variables between the groups. Results: As expected, analysis showed no significant difference between players in basic morphological variables according playing position (DEF-184.9±5.8 ?cm and 83.6±7.5?kg; MF=180.3±6.3 cm and 78.4±5.7 kg; AT=180.9±6.0 cm and 77.9±8.2 kg). In the same time, significant difference we didn`t find in parameters of maximal heart rate (DEF=190.5±12.9 bpm, MF=190.5±7.3 bpm and AT=191.0±8.1 bpm), heart rate on the anaerobic threshold (DEF=149.0±11.7 bpm, MF=169.7±7.9 bpm and AT=170.5±8.8 bpm), maximal relative oxygen uptake (DEF=57.1±4.7 ml/kg/min, MF=56.6±3.4 ml/kg/min and AT=57.1±4.6 ml/kg/min) and relative oxygen uptake on the anaerobic threshold (DEF=48.8±4.4 ml/kg/min, MF=55.6±30.4 ml/kg/min and AT=48.7±3.7 ml/kg/min). Looking at research in general, such results we can ascribe last trends in modern football which from each player requirements equal energetic demand. Conclusion: There are differences between defenders, middle field players and attackers, but they are not significant. Such results are consequence of requirements that modern football demands from football players. In modern football, each player participates in all phases of the game. So, we can say that the old style of playing football, that divides team into two main groups, defenders and attackers, is history.